Not the slightest chance : the defence of Hong Kong, 1941 - Banham, Tony, 1959- (Hong Kong University Press, 2003)
The book assembles a phase-by-phase, day-by-day, hour-by-hour, and death-by-death account of the battle. It considers the individual actions that made up the fighting, as well as the strategies and plans and the many controversies that arose.